2022
DOI: 10.1111/joim.13532
|View full text |Cite
|
Sign up to set email alerts
|

The risk of renal comorbidities in celiac disease patients depends on the phenotype of celiac disease

Abstract: Background. An increased risk of kidney disease in patients with celiac disease has been reported, but the association has remained obscure. Only few studies have investigated the association between renal comorbidities and dermatitis herpetiformis, a cutaneous manifestation of celiac disease.Objectives. We investigated whether patients with different phenotypes of celiac disease are at higher risk of kidney diseases than age-and sex-matched references.Methods. The diagnoses of glomerulonephritis, diabetic nep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…We have read with great interest the recently published article by Nurmi et al [1]. The authors performed a cohort study with long-term data and reported that celiac-disease patients were at increased risk of kidney disease, which was dependent on the celiac-disease phenotype.…”
Section: Regarding: the Risk Of Renal Comorbidities In Celiac Disease...mentioning
confidence: 99%
“…We have read with great interest the recently published article by Nurmi et al [1]. The authors performed a cohort study with long-term data and reported that celiac-disease patients were at increased risk of kidney disease, which was dependent on the celiac-disease phenotype.…”
Section: Regarding: the Risk Of Renal Comorbidities In Celiac Disease...mentioning
confidence: 99%
“…Dear Editor, We thank Dr Han and Dr Gao for their interest and important comments [1] regarding our recently published article in the Journal of Internal Medicine [2]. First, they requested more consideration with matching factors.…”
Section: Authors' Reply: the Risk Of Renal Comorbidities In Celiac Di...mentioning
confidence: 99%
“…The prevalence of CD is increased among individuals with chronic kidney disease (CKD), as evidenced by current studies ( 15 ). Also, an increased risk of end-stage renal disease (ESRD) has been associated with CD ( 16 ).…”
Section: Introductionmentioning
confidence: 98%